Construção de visualizações de matrizes origem-destino no cenário do tráfego urbano com foco em avaliação de usabilidade - Gondim, Halley Wesley Alexandre Silva (2016)
Most of the medium and large cities in the world suffer from the problems related to the growth of the number of vehicles. Congestion, air pollution and weather are some examples of these problems, today constantly reminded of the great damage done to citizens. The use of Information Visualization techniques can serve to support the analysis of these problems and help identify viable and effective solutions for them. On the other hand, the application of Information Visualization to the problems of urban traffic is still a poorly explored area and generally focused on simple aspects of traffic. The present thesis thus addresses the lack of studies in this area, especially in the representation of data related to origin-destination (OD) matrices. In order to do so, a specific classification is proposed for visualizations aimed at the urban traffic scenario, with the purpose of facilitating the identification of works and authors related to the area. In addition, there is the creation of new visualizations, directed to OD arrays, in order to offer different alternatives in the representation of traffic data. Finally, an approach is proposed to evaluate visualizations of OD matrices and correlated information, with the intention of offering adequate feedback to interface designers and enabling the creation of more effective visualizations.